2002
DOI: 10.1021/jp0202284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collision and Vibrational Energy on the Reaction of CH3CHO+(ν) with C2D4

Abstract: The reaction of acetaldehyde cations with ethene has been studied as a function of collision energy and acetaldehyde vibrational state. REMPI through different vibrational levels of the B̃ electronic state is used to produce CH3CHO+ with controlled excitation in different vibrational modes. Reactions are studied in a guided ion beam instrument, including measurements of product ion recoil velocity distributions. In addition, we calculated the structures and energetics of 13 different complexes that potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…These are not isolated examples. Similar effects have been observed for other ion-molecule systems ranging in size from six atoms (e.g., OCS + + OCS [63]) to much larger systems such as reaction of C 6 H 5 OH + with NH 3 [64] or of acetaldehyde with a number of small molecules [65][66][67][68]. As in the examples presented, strong dynamical effects are observed even in reactions that are exoergic, with no activation barriers in excess of the reactant energy.…”
Section: Discussionsupporting
confidence: 64%
“…These are not isolated examples. Similar effects have been observed for other ion-molecule systems ranging in size from six atoms (e.g., OCS + + OCS [63]) to much larger systems such as reaction of C 6 H 5 OH + with NH 3 [64] or of acetaldehyde with a number of small molecules [65][66][67][68]. As in the examples presented, strong dynamical effects are observed even in reactions that are exoergic, with no activation barriers in excess of the reactant energy.…”
Section: Discussionsupporting
confidence: 64%
“…The latter case seems to be the most common at the higher T com values they studied, however in some cases it was shown that increasing the vibrational energy of the ion decreased the efficiency of T ! V energy transfer in the collisions (Kim, Liu, & Anderson, 2002), a result seemingly in contradiction to the idea that energy transfer should be easier the more anharmonic the vibration (Process 2). They have even shown that for CID processes that seemingly occur statistically (i.e., are mediated by long-lived complexes that have lifetimes consistent with statistical theories), one cannot guarantee that all internal energy is statistically distributed, since vibrationally selected ions still show dynamical effects.…”
Section: Velocity Mapping Studiesmentioning
confidence: 76%
“…Anderson and co-workers have explored the dynamics of ion-molecule reactions as a function of collision energy and vibrational energy in the reacting ion, and in doing so have explored the efficiency of translational-to-internal energy conversion in the 0-$10 eV T com range (Yang et al, 1991;Kim, Liu, & Anderson, 2002;Liu, Devener, & Anderson, 2002Liu, Devener, & Anderson, 2005;Liu et al, 2006a,b). They use supersonic expansion to create molecules that are internally cold, followed by resonance-enhanced multiphoton ionization (REMPI) to generate projectile ions with particular vibrational modes excited by one or two quanta of energy.…”
Section: Velocity Mapping Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In contrast, for CT of CH 3 CHO ϩ with C 2 D 4 (⌬ r Hϭ0.28 eV), the E vib ͑fit)/E vib ͑actual) ratio was ϳ18%, irrespective of the vibrational state. 34 Finally, for CT of OCS ϩ with C 2 H 2 (⌬ r H ϭ0.23 eV) the vibrational efficiency is quite mode-specific. E vib ͑fit)/E vib ͑actual) is ϳ100% for 3 ϩ ͑C-S stretch, 87 meV͒, and essentially 0% for both 1 ϩ ͑C-O stretch, 256 meV͒ and 2 ϩ ͑bend, 62 meV͒ excitation.…”
Section: B Threshold Energy Dependence and The Effects Of Vibrationamentioning
confidence: 97%